The Protective Effects of 18β-Glycyrrhetinic Acid on Imiquimod-Induced Psoriasis in Mice via Suppression of mTOR/STAT3 Signaling - Haiming Chen; Huazhen Liu; Bin Tang; Yuchao Chen; Ling Han; Jingjie Yu; Yuhong Yan; Chuanjian Lu (Journal of Immunology Research)
Psoriasis is recognized as an autoimmune and inflammatory dermatosis, which is estimated to affect 2-3% of the population worldwide. 18β-Glycyrrhetinic acid (GA), one of the main ingredients of Licorice (Glycyrrhiza glabra L.), has been shown to have numerous pharmacological effects such as antioxidative, antitumor, and anti-inflammatory activities. However, it remains to be explored whether GA has antipsoriatic effect on psoriasis. In this study, we evaluated the protective effect of GA on psoriasis and its mechanisms of action in imiquimod-induced psoriasis-like mouse model. Results indicated that GA dramatically improved psoriatic lesions and reduced psoriasis area and severity index scores. GA also suppressed the mRNA levels of IL-6, TNF-α, IL-17, IL-23, and IL-1β in the skin and increased the proportion of CD4+ Foxp3+ regulatory T cells (Tregs) in both lymph nodes and spleens. Its anti-inflammatory and immunomodulatory activities may be related to its suppression of the STAT3 and mTOR signaling. In conclusion, GA ameliorated the symptoms of psoriasis, at least in part, through inhibition of inflammatory cytokines and STAT3/mTOR signaling and activation of Tregs in both lymph nodes and spleens. These effects are expected to be beneficial in the treatment and prevention of psoriasis.